Questions about the Priestly and Missionary Vocation and the Ordination of John Nepomucene Neumann - Svoboda, Rudolf (The catholic historical review, 2023)
Several publications are devoted to John Nepomucene Neumann (1811-60), bishop of Philadelphia and the first American male saint. The emphasis in these texts is mainly on his time in the United States since 1836. On the contrary, the time of his youth and maturation in Europe, in Bohemia, is somewhat neglected. However, his decision to pursue the priesthood, becoming a missionary, and going to the United States before receiving holy orders were the most significant events preceding everything else which followed in the young man's life. In the hagiographic and professional literature, these decisions are mentioned in various contexts and often contradict each other. Based on research from contemporary sources stored in European and American archives, this study shows the accurate chronology of Neumann’s decisions, as well as their demonstrable causes, based not only on his decisions but also on the specific situation in his native Diocese of Budweis, and also complicated relations between the Catholic Church and the state.